Nutritional management of moderate–late preterm infants: Survey of current practice. (27th August 2018) - Alexander, Tanith; Bloomfield, Frank H
Abstract : Aim: Moderate–late preterm (MLPT) babies account for over 80% of preterm babies born world‐wide. Many MLPT babies require early nutritional support while full sucking feeds are established, but there is little evidence to guide practice. We aimed to determine current practice in Australia and New Zealand. Methods: An electronic survey was sent to neonatal clinical directors within the Australia and New Zealand Neonatal Network requesting dissemination to colleagues involved in the care of MLPT babies (32–35 +6 weeks' gestation). The questionnaire asked about respondents' nutritional management of MLPT babies and included scenarios for both moderate‐ (MPT) and late preterm (LPT) babies. Results: There were 83 respondents. While waiting for mothers' milk to meet prescribed fluid volumes, 61% (MPT) to 53% (LPT) of respondents would provide dextrose 10% as the first nutritional support, with 15% (MPT) to 38% (LPT) providing infant formula. Of clinicians providing 10% dextrose, 31% (MPT) to 49% (LPT) were happy to do so for ≥3 days, with 5% comfortable doing so for 5 days in moderately preterm babies, before providing additional support. This additional support was infant formula in 73% (MPT) to 90% (LPT) of respondents. Conclusions: There is variation in the nutritional management of MLPT infants amongst neonatal clinicians, likely due to the lack of evidence from randomised controlled trials on which to base clinical practice. The majority of clinicians are happy providing only dextrose 10% for up to 2–3 days despite this form of nutritional support containing only carbohydrate.